2017
DOI: 10.1038/onc.2017.400
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of RAC1-driven malignant melanoma by group A PAK inhibitors

Abstract: Activating mutations in the RAC1 gene have recently been discovered as driver events in malignant melanoma. Expression of this gene is associated with melanocyte proliferation, and melanoma cells bearing this mutation are insensitive to BRAF inhibitors such as vemurafenib and dabrafenib, and also may evade immune surveillance due to enhanced expression of PD-L1. Activating mutations in RAC1 are of special interest, as small molecule inhibitors for the RAC effector p21-activated kinase (PAK) are in late-stage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 30 publications
6
43
0
Order By: Relevance
“…Ras‐related C3 botulinum toxin substrate 1 (RAC1) is a pleiotropic regulator of many cellular processes, including the cell cycle, cell‐cell adhesion, motility, and of epithelial differentiation . Recent studies showed that RAC1 worked as an oncogene in many tumors, including breast cancer, melanoma, and liver cancer . In the present study, we for the first time found that RAC1 was a direct target of miR‐365.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Ras‐related C3 botulinum toxin substrate 1 (RAC1) is a pleiotropic regulator of many cellular processes, including the cell cycle, cell‐cell adhesion, motility, and of epithelial differentiation . Recent studies showed that RAC1 worked as an oncogene in many tumors, including breast cancer, melanoma, and liver cancer . In the present study, we for the first time found that RAC1 was a direct target of miR‐365.…”
Section: Discussionsupporting
confidence: 63%
“…37 Recent studies showed that RAC1 worked as an oncogene in many tumors, including breast cancer, melanoma, and liver cancer. [38][39][40] In the present study, we for the first time found that RAC1 was a direct target of miR-365.…”
Section: Discussionsupporting
confidence: 58%
“…From a pharmacological standpoint, the Rac1 P29S mutation is associated with resistance to Raf inhibitors and PD-L1 up-regulation, thus contributing to evading immune surveillance and potentially serving as a predictive biomarker for therapy resistance in melanoma (42, 43). A recent interesting study revealed that Rac1 mutant melanoma cells are highly sensitive to Pak inhibition, a result consistent with the augmented engagement of Rac effectors by the Rac1 P29S mutant (44). Other described gain-of-function mutants in human tumors include Rac1 Q61R (prostate cancer) and Rac1 A159V (head and neck cancer) (45).…”
Section: Aberrant Rac Expression and Activity In Human Cancermentioning
confidence: 61%
“…As indicated above, Rac1 P29S mutated melanoma cells are resistant to clinical BRAF inhibitors but highly sensitive to Pak inhibition (42, 44), and they exhibit elevated expression of PD-L1, a ligand of the checkpoint protein PD-1 that plays a fundamental role in immune evasion (43). Conceivably, pharmacological inhibition of Rac could be beneficial in combination with anti-PD-L1 monoclonal antibodies or other immune checkpoint inhibitors.…”
Section: Concluding Remarks - Rac and Tumor Susceptibility: From Biocmentioning
confidence: 99%
“…Defective growth was reversed by PAK and MEK inhibitors, suggesting that these may be useful to prevent the developmental effects of RAC1 P29S mutations. 9 In addition, we and others have reported that tumors and human melanoma cell lines bearing RAC1 P29S mutations are resistant to BRAF inhibitors but are sensitive to PAK and MEK inhibitors. 9,10 In addition to PAKs, PI3Ks represent a second recognized effector for RAC1 11 .…”
Section: Introductionmentioning
confidence: 88%